Recensions / Book Reviews: Constas and Platias, Diasporas in World Politics: The Greeks in Comparative Perspective - Evriviades, Marios (Études helléniques / Hellenic Studies, 1994)
DIMITRI C. CONSTAS AND ATHANASSIOS G. PLATIAS EDITORS, DIASPORAS IN WORLD POLITICS: THE GREEKS IN COMPARATIVE PERSPECTIVE, FORWARD BY JAMES ROSENAU, LONDON: THE MACMILLAN PRESS LTD, 1 993, XXI+ 239PP.